Cardiopulmonary resuscitation: knowledge amongst Nepalese health personnel - Amatya, M; Gorkhali, B (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: The role of effective basic life support (BLS) and cardiopulmonary resuscitation (CPR) is established. Reports on CPR knowledge assessment in Nepal are few and underline the gross lack of CPR knowledge. Material and Methods: A cross-sectional descriptive study was conducted among residents, students, and teachers in a few Nepalese health institutions. A questionnaire based on BLS guidelines 2010 was used, incorporating total 30 questions. Results: Total 145 complete responses (63 females, 82 males) were obtained and analyzed. Mean and median of correct answers was 18 out of 30 (60%, range 3-26); 9% could identify the correct sequence of action from a given set of 7 CPR steps. By ANOVA, score correlated significantly with the background of person (scores highest 19 in ‘clinical’ group and 18 in ‘dentistry’ to 16.38 in ‘nursing’ and 15.09 in ‘non-clinical’; p=0.000) but not with other variables (sex, age, designation, academic degree, institution, and previous CPR training). Conclusion: Lack in CPR knowledge and awareness are reported worldwide. Findings of this study are similar. Although those with clinical background had better knowledge, poor correlations with other variables indicate lack of importance being given to CPR knowledge and skill by most people, even those working in big health institutions of the country. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):25-30